2018
DOI: 10.35790/jbm.10.2.2018.20087
|View full text |Cite
|
Sign up to set email alerts
|

Korelasi antara Gambaran Spektral Doppler Arteri Tibialis Posterior dan Arteri Dorsalis Pedis dengan Skor PEDIS pada Penderita Ulkus Kaki Diabetik

Abstract: Diabetic foot ulcer is still a major health problem worldwide due to its increasing prevalence. This study was aimed to prove the correlation between PEDIS score and vascular Doppler examination performed on dorsalis pedis and posterior tibial arteries of patients with diabetic foot ulcers. This was an observational study with a cross sectional design. The results showed that during the period of August 2017 until January 2018, there were 62 patients with diabetic foot ulcers at the wards of Surgery Department… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
1
0
0
2
Order By: Relevance
“…The results of this study found that the incidence of diabetic foot ulcers was the most common in the age group with a mean of 60.46 years (Table 2). This is in line with research by Zaine et al 11 and Limpeleh et al 12 who reported that the incidence of diabetic foot ulcers occurred in the 6th decade. Elderly patients usually have limited movement, reduced visual acuity and other disease problems so that the incidence of diabetic foot ulcers is at high risk for elderly patients.…”
Section: Discussionsupporting
confidence: 92%
“…The results of this study found that the incidence of diabetic foot ulcers was the most common in the age group with a mean of 60.46 years (Table 2). This is in line with research by Zaine et al 11 and Limpeleh et al 12 who reported that the incidence of diabetic foot ulcers occurred in the 6th decade. Elderly patients usually have limited movement, reduced visual acuity and other disease problems so that the incidence of diabetic foot ulcers is at high risk for elderly patients.…”
Section: Discussionsupporting
confidence: 92%
“…7 Pulse Wave Handheld Doppler (PWHD) vaskular merupakan modalitas yang mudah tersedia dan non-invasif untuk evaluasi arteri ekstremitas inferior dan dapat mendeteksi tingkat keparahan gangguan aliran darah atau PAP yang sedang berlangsung, 12 dengan sensitivitas 42,8% dan spesifitas 97,5%. 13 Dalam praktik klinis, PWHD telah terbukti memiliki tingkat reliabilitas yang tinggi. 12 Dalam melakukan analisis audio, bentuk gelombang Doppler non-patologis dianggap multifasik, yang mencakup bunyi bifasik (dua) atau trifasik (tiga).…”
Section: Pendahuluanunclassified
“…Didapatkan pasien dengan leukositosis sebanyak 87,8% dan hipoalbuminemia sebanyak 90,9%. Hal ini sesuai dengan hasil penelitian Limpeleh 13 di Manado yang menunjukkan tingginya jumlah pasien kaki diabetik dengan keadaan leukositosis dan hipoalbuminemia. Hal ini merupakan momok untuk penyakit kaki diabetik di negara berkembang seperti Indonesia dan merupakan salah satu prediktor kesadaran terhadap penyakit DM yang rendah.…”
Section: Diskusiunclassified